A Common Polymorphism Flanking the ATG Initiator Codon of GPIbα Does not Affect Expression and Is not a Major Risk Factor for Arterial Thrombosis - Corral, J.; Lozano, M. L.; González-Conejero, R.; Martínez, C.; Iniesta, J. A.; Rivera, J.; Vicente, V. (Thrombosis and Haemostasis, 2000)
The platelet membrane glycoprotein (GP) Ibα plays a key role in the initial formation of thrombi. Polymorphisms (VNTR and HPA-2) in this receptor are associated with increased risk of coronary heart disease (CHD) and cerebral vascular disease (CVD). We investigated whether a recently described polymorphism (S/R), due to a single base change (T → C) five nucleotides upstream the initiator codon of GPIbα, might influence the expression of the protein, and be implicated in the development of arterial thrombosis.One hundred and thirty nine healthy individuals provided blood samples for DNA analysis of platelet GPIbα polymorphisms, and for flow cytometric analysis of the surface expression of the receptor. A group of 20 S/R normal individuals and an identical number of S/S participants, age and sex matched, was investigated for the analysis of the density of various platelet receptors. The distribution of the S/R polymorphism was also analyzed in two case/control studies including 104 CVD patients, 101 CHD patients, and one control age, sex, and environmental risk factors matched for each case patient. Surface density of GPIbα showed no wide variations between individuals, was not influenced by the presence of S or R alleles, nor associated with the VNTR or HPA-2 polymorphisms. The prevalence of the S/R genotype among CVD and CHD patients was not distinct from that in the control groups. We conclude that the S/R polymorphism of GPIbα, flanking the initiator codon of the receptor, does not seem to be associated with surface levels of the protein, and is not an independent risk factor for arterial thrombosis.
Keywords: GPIbα; polymorphism; risk factor; arterial thrombosis; platelet